Programmatic advertising: An exegesis of consumer concerns. (March 2021) - Samuel, Anthony; White, Gareth R.T.; Thomas, Robert; Jones, Paul
Abstract: Programmatic advertising is a nascent and rapidly growing information technology phenomenon that reacts to, and impacts upon, consumers and their behavior. Despite its popularity and widespread use, research in the area remains scant and our current knowledge is based upon a preponderance of practitioner-generated literature. This study contributes to our understanding of this technology by unpacking the means by which it functions and interacts with consumers. The study draws upon paradox theory to deconstruct programmatic advertising's inherent tensions as dilemmas and dialectics. Adopting organisations are faced with the dilemma of pursuing the acquisition of increasingly detailed information in order to provide more personalized offerings, yet doing so increases the likelihood of creating a sense of fear and distrust among consumers. The automation of personalized advertising appears attractive yet presents the dilemma that adverts may be inappropriately placed. Finally, the true cost/benefit of programmatic advertising is unclear, and adopters, platform providers and developers need to engage in dialectic in order to fully understand and communicate its financial implications. Through identifying these fundamental constraints, the study affords pathways for programmatic system actors to ameliorate their, and their customers' concerns. Highlights: Provides an overview of the nascent research area of Programmatic Advertising. Contributes further insights of Programmatic Advertising by clarifying its functions and consumer interaction. Uses Paradox Theory to deconstruct Programmatic Advertising's inherent tensions as dilemmas and dialectics.